Autonomous weapons systems & international humanitarian law: principles, responsibilities and state behavior - Eidhammer, Jonas Bruun (Riga Graduate School of Law, 2018)
The thesis aims to analyze the controversies surrounding autonomous weapons systems (AWS) by answering the question: Are AWS are compatible with international humanitarian law (IHL) and should they be regulated? The question is divided into two main parts: (1) are autonomous weapons systems compatible with the principles of jus in bello and who can be held responsible if AWS violate IHL, and (2) should states attempt to regulate their use?
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; International humanitarian law